2019
DOI: 10.1136/neurintsurg-2019-015035
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed stenting for intracranial atherosclerotic artery stenosis with ischemic stroke

Abstract: ObjectiveTo evaluate the clinical outcomes of early stenting (≤14 days) or late stenting (>14 days) in patients who underwent intracranial stent placement.MethodsPatients with ischemic stroke caused by 70–99% intracranial atherosclerotic stenosis combined with poor collaterals were enrolled. The early stenting group, who underwent stenting within 14 days of last ischemic symptoms, were compared with the late stenting group who underwent stenting >14 days from last ischemic symptom. The patients were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Stent placement for ICAS was inferior to the medical treatment group in the SAMMPRIS and VISITIT trials, but from Asia, where the prevalence of atherosclerotic cerebral artery stenosis is high, better results have been reported. [12][13][14] Although the effectiveness of angioplasty for this disease is not yet clear, the most significant point is to select appropriate patients and reduce complications to enhance the therapeutic effect. Patients with hypoperfusion stroke secondary to ICAS who continue to have symptoms despite double antiplatelet therapy, statins, and tight control of hypertension and diabetes mellitus will be a good indication for angioplasty or stenting.…”
Section: Discussionmentioning
confidence: 99%
“…Stent placement for ICAS was inferior to the medical treatment group in the SAMMPRIS and VISITIT trials, but from Asia, where the prevalence of atherosclerotic cerebral artery stenosis is high, better results have been reported. [12][13][14] Although the effectiveness of angioplasty for this disease is not yet clear, the most significant point is to select appropriate patients and reduce complications to enhance the therapeutic effect. Patients with hypoperfusion stroke secondary to ICAS who continue to have symptoms despite double antiplatelet therapy, statins, and tight control of hypertension and diabetes mellitus will be a good indication for angioplasty or stenting.…”
Section: Discussionmentioning
confidence: 99%
“…This may be one of the reasons for the lower rate of complications in the PTAS group. A study showed that patients with delayed (> 14 days) ICAS stenting had a lower risk of longterm cerebral vascular events than those in whom the procedure was carried out < 14 days of the qualifying event (20). Although there was no significant difference in stroke rates from the 1st to 12th month between the SMT (9/62, 14.5%) and PTAS groups (13/174, 7.5%), there was a significant difference in the rate of severe stroke between the PTAS (0%) and SMT groups (9.7%).…”
Section: Discussionmentioning
confidence: 99%
“…DSA was performed for all patients, and the strategy of endovascular treatment was decided according to the site and characteristics of the target lesions and based on the operators' experience and preference ( 3 , 9 ). In general, Apollo BMS (MicroPort Medical, Shanghai, China) was preferred in lesions with straightforward arterial access.…”
Section: Methodsmentioning
confidence: 99%
“…Intracranial atherosclerotic stenosis (ICAS) is a common etiology of stroke worldwide, with the highest prevalence being in Asian, Hispanic, and African populations and ICAS accounting for approximately half of transient ischemic attacks (TIAs) and ischemic strokes in Asian populations ( 1 , 2 ). The annual risk of recurrent stroke in patients with ICAS varies from 4 to 40% and is especially high in patients with severe stenosis (70–99%), for which the rate is ~23% despite best medical therapy (BMT) ( 3 , 4 ). Endovascular treatments, including percutaneous transluminal angioplasty (PTA) with balloon dilatation (BD) alone and PTA with stenting (PTAS) using either a balloon-mounted stent (BMS) or a self-expanding stent (SES) have been developed and widely used in some countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation